PEDAGOGICAL IDEAS AND VALUES THROUGH THE CREATIVITY OF DJORDJE TASIC (Heritage, 2024)
The author analyzes the pedagogical aspects and ideas in the prolific creative work of Djordje Tasic, a renowned Serbian educator, lawyer, theorist, and sociologist. As an exceptional educator and professor, Tasic excelled in imparting his knowledge and thoughts to younger generations, making abstract concepts understandable and relatable. He viewed his work as a life and destiny activity, not just a professional task. The paper examines both the pedagogical aspects of his creativity and connections with the ideas and values of significant Serbian educators such as Vincenije Rakic and Sreten Adzic. Tasic, as a prominent professor and advocate for democracy, is remembered as an expert in the field of legal sciences and sociology. He was an inspiration to younger generations on how to strive for truth and humanity in science, as well as benevolence in life, which speaks to his noble nature and humanity. His life, largely dedicated to science, makes him a giant who contributed to the enrichment of intellectual heritage, especially in the context of the educational system.
Keywords: pedagogical work, knowledge, critical thinking, humanity, national consciousness